Regulation of the Development and Function of B Cells by ZBTB Transcription Factors - Zhu, Can; Chen, Ge; Zhao, Ying; Gao, Xiao-Ming; Wang, Jun (Frontiers in Immunology, 2018)
The large ZBTB family comprises a diverse group of transcriptional factors. Several ZBTB proteins have emerged as critical factors that regulate the lineage commitment, differentiation and function of lymphoid cells as well as many other developmental events. For instance, dysfunctions of ZBTB20 or ZBTB24 have been linked to multisystem failures in humans. Within the B-cell lineage, BCL6, ZBTB7A, ZBTB17 and ZBTB1 regulate the development/differentiation of B cells in both bone marrow and peripheral lymphoid organs, while ZBTB20 and ZBTB32 seem to mainly impact the maintenance of terminally-differentiated plasma cells. Given the importance of B cells in the prevention and treatment of infectious or autoimmune disorders, we herein summarize the roles of seven ZBTB family members (BCL6, ZBTB7A, ZBTB17, ZBTB20, ZBTB32, ZBTB1 and ZBTB24) in the development, differentiation and function of B cells as well as the underlying molecular mechanisms.